2020
DOI: 10.2147/trrm.s264872
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude, and Willingness Towards Organ Donation Among Medical and Health Sciences Students in Central Region, Saudi Arabia</p>

Abstract: In this modern era, organ transplantation has become an important treatment method for certain diseases. Doctors and allied health professionals play important roles in continuing its advocacy and sharing knowledge within the community; thus, educating the public on organ donation is paramount. The present study aimed to understand the knowledge, attitude, and willingness toward organ donation of medical and health sciences students. Materials and Methods: We conducted a cross-sectional questionnaire-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
5
13
0
Order By: Relevance
“…In a way that females showed higher knowledge and more positive attitudes toward organ donation. This result is consistent with the findings of Almutairi et al study in Saudi Arabia ( 19 ). In the contrary, the results of the study by Wolide et al indicated that male students had higher knowledge score ( 18 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In a way that females showed higher knowledge and more positive attitudes toward organ donation. This result is consistent with the findings of Almutairi et al study in Saudi Arabia ( 19 ). In the contrary, the results of the study by Wolide et al indicated that male students had higher knowledge score ( 18 ).…”
Section: Discussionsupporting
confidence: 94%
“…The present study illustrated that the most used source of information regarding organ donation and transplantation was TV. The results of several studies done in Iran and other foreign studies were consistent to this study and in all of them TV was found as the main source of information ( 17 , 19 , 27 34 ). The results of the study carried out by Manzari et al among families with brain dead patient, pointed to the effective role of TV in decision-making of family regard donating their family member organs ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority had no sufficient information about corneal donation and did not know how or where to apply to register as a cornea donor A significant correlation between participants' knowledge and willingness to donate The largest perceived barrier was the lack of information on where to donate or register as donors The main motive to donate was the religious belief of doing good and being charitable with their organs Almutairi [94] Students (n = 425) from Central province Medicine and physiotherapy students in their final year scored higher knowledge, attitudes, and willingness towards organ donation compared to dentistry, nursing, and paramedical counterparts Females scored higher than males in all the three domains of knowledge, attitude, and willingness toward organ donation Alnajjar et al [30] Students (n = 113) from Jeddah The majority were aware of the importance of organ donation More than half of the participants expressed a willingness to donate the organs of family members if they were to be diagnosed with brain death…”
Section: Resultsmentioning
confidence: 99%
“…In Saudi Arabia (KSA), the approximate number of donated organs is about 2-4 million as compared to the more than 20 million population in countries like the United States and Spain [5][6][7]. The steeply expanding need between patients who need transplantation and the availability of qualified donors is a significant reason for concern that mandates further attention [8][9]. As indicated by accessible assessments, a total of 146,993 organ donations were made all around the world in 2018 [10].…”
Section: Introductionmentioning
confidence: 99%